Sestrin2 in diabetes and diabetic complications - Zhang, Xiaodan; Luo, Zirui; Li, Jiahong; Lin, Yaxuan; Li, Yu; Li, Wangen (Frontiers in Endocrinology, 2023)
Diabetes is a global health problem which is accompanied with multi-systemic complications. It is of great significance to elucidate the pathogenesis and to identify novel therapies of diabetes and diabetic complications. Sestrin2, a stress-inducible protein, is primarily involved in cellular responses to various stresses. It plays critical roles in regulating a series of cellular events, such as oxidative stress, mitochondrial function and endoplasmic reticulum stress. Researches investigating the correlations between Sestrin2, diabetes and diabetic complications are increasing in recent years. This review incorporates recent findings, demonstrates the diverse functions and regulating mechanisms of Sestrin2, and discusses the potential roles of Sestrin2 in the pathogenesis of diabetes and diabetic complications, hoping to highlight a promising therapeutic direction.